Utilizing the somatosensory system via vibratory stimulation to mitigate knee pain during walking: Randomized clinical trial - Fischer, Arielle G.; Erhart-Hledik, Jennifer C.; Asay, Jessica L.; Chu, Constance R.; Andriacchi, Thomas P. (Gait & posture, 2020)
•Activating pain and sensory pathways can mitigate pain and restore muscle function.•Crossover study tests effect of active (vibration) and passive (pressure) treatment.•Wearing active treatment for 4 weeks caused significant improvement in pain.•Subjects with low baseline knee flexion had greater increases in flexion.•Novel approach for exercise therapy by gating pain and reducing muscle inhibition. Pain and proprioception deficits are often associated with knee pathologies and resultant quadriceps muscle inhibition. There is a need for new approaches to mitigate active knee pain and restore muscle function during walking. Activating properties of the somatosensory system with common pain and sensory pathways offers a novel opportunity to enhance quadriceps function during walking. Conduct a controlled clinical trial that investigates the effects of applying intermittent vibrational cutaneous stimulation during walking on knee pain and symptoms and their correlations to gait parameters. This longitudinal controlled cross-over clinical study included thirty-two patients randomly and blindly assigned to active Treatment A and passive Treatment B for 4 weeks with a 2-week washout period between treatments. Subjects when wearing active Treatment A for 4 weeks had significant (p = 0.04) improvement in patient reported outcomes, while they had no significant differences with passive Treatment B (p > 0.7) compared to the no treatment condition. For Treatment A, subjects with low knee flexion moment and knee flexion angle in no-treatment condition exhibited the greatest increase in knee flexion moment/angle in the active treatment condition (R > 0.57, p < 0.001). These changes in gait measures were correlated significantly to changes in pain. This clinical trial indicates that knee pain can be reduced, and gait improved in a manner that enhances quadriceps function by applying intermittent cutaneous stimulation during gait in patients following knee injury or disease. The correlation between decreased pain and improved gait suggests that rehabilitation and exercise therapy may benefit from this treatment.